A RARE CASE OF HYPERGLYCAEMIA HEMICHOREA IN A NEWLY DIAGNOSED TYPE 1 DIABETES MELLITUS PATIENT - Chua, Yi Jiang; Hussein, Zanariah (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Hemichorea is an uncommon presentation of hyperglycaemia. Reported cases are usually among elderly women with poorly controlled Type 2 Diabetes Mellitus in the Asian population. The difficulty of management of such cases is often due to unfamiliarity hemochorea as an associated symptom of hyperglycemia. We report the case of a 39-year-old female, who presented with left hemichorea associated with hyperglycaemia. CASE A 39-year-old female, with history of Grave’s Disease, presented with 1-week history of hemichoreoform movement of the left upper limb and lower limb. Upon presentation, her vital signs were normal and Glasgow Coma Scale (GCS) was 15. Bedside capillary blood glucose (CBG) was 21.8 mmol/L and serum plasma ketone was 2.8mmol/L, however venous blood gas was normal. Computed tomography (CT) of the brain was done revealing unilateral right caudate nucleus and putamen calcification. This patient was managed with variable rate insulin infusion initially, and overlapped with basal bolus insulin when she was more stable. Her hemichoreoform movement did not improve despite normalization ofthe sugar levels. Clonazepam was added to control her symptoms but only yielded partial improvement. After 1-week of benzodiazepine treatment, haloperidol was added to further control the symptoms. She was discharged with insulin therapy and 2 months upon review in the outpatient clinic, her symptoms were well-controlled and she was able to ambulate independently. Even though phenotypically she appeared to have Type 2 Diabetes Mellitus, her diabetes autoantibodies (anti-islet cell and anti-glutamic acid decarboxylase) were strongly positive. Her HbA1c had improved from 17.0% to 6.8% within 3 months’ time. CONCLUSION Hemichorea is a rare presentation of hyperglycaemia. However, it is important to recognize it, as prompt glycaemic control can alleviate the symptoms alongside with symptomatic control medications such as benzodiazepine and dopamine receptor antagonist.